Women's Wisdom : 3,577 Tips, Facts & Advice Every Woman Must Know About Her Health and Lifestyle - Edited By Faelten, Sharon (U.S.A Rodale, 2000)
Include Index and Illustrations.
Keywords: Women--Health and Hygiene